Combined α-programmed death-1 monoclonal antibody blockade and fractionated radiation therapy reduces tumor growth in mouse EL4 lymphoma. Issue 5 (4th May 2019) - Lin, Xiuyun; Zeng, Tao; Xiong, Jiani; Zhang, Qiong; Jiang, Pan; Li, Xiufeng; Lin, Shuchun; Xu, Qianqian; Weng, Huanjiao; Lai, Haichun; Gong, Huichun; Lin, Jinxiang; et al.
ABSTRACT: The programmed death (PD) pathway is frequently present in the tumor microenvironment (TME) and suppresses tumor immunity by inhibiting the activity of tumor-infiltrating lymphocytes (TILs), particularly, CD8 + lymphocytes. PD immunotherapy involves stimulation of the immune response in the region surrounding the tumor but is insufficient to prevent tumor progression. Therefore, in this study, we examined the effects of combined PD immunotherapy with fractionated radiotherapy (RT) on antitumor immunity and tumor growth in lymphoma. The immune cell profiles of the TME, blood, and secondary lymphoid organs were determined 7 days after treatment. Four combination therapies were compared. The synergistic effects of αPD-1 mAb and fractionated RT on increased CD8 + lymphocytes in the TME, blood, and secondary lymphoid organs led to substantial tumor regression in mouse EL4 lymphoma, both locally and systemically. Fractionated RT for 4 days followed by αPD-1 mAb therapy was significantly superior to other schemes in terms of overall survival rates and curative rates in xenograft model mice. Our data indicated that substantial immune responses occurred following combination therapy with fractionated RT and αPD-1 mAb immunotherapy. Our findings provide important insights into the use of RT plus αPD-1 mAb as an efficacious combinatorial therapy.